Signaling Mechanisms in Cortical Axon Growth, Guidance, and Branching - Kalil, Katherine; Li, Li; Hutchins, B.Ian (Frontiers in Neuroanatomy, 2011)
Precise wiring of cortical circuits during development depends upon axon extension, guidance and branching to appropriate targets. Motile growth cones at axon tips navigate through the nervous system by responding to molecular cues, which modulate signaling pathways within axonal growth cones. Intracellular calcium signaling has emerged as a major transducer of guidance cues but exactly how calcium signaling pathways modify the actin and microtubule cytoskeleton to evoke growth cone behaviors and axon branching is still mysterious. Axons must often pause in their outgrowth while their branches extend into targets. Some evidence suggests a competition between growth of axons and branches but the mechanisms are poorly understood. Since it is difficult to study growing axons deep within the mammalian brain, much of what we know about signaling pathways and cytoskeletal dynamics has come from studies of axonal growth cones, in many cases from non-mammalian species, growing in tissue culture. Consequently it is not well understood how guidance cues relevant to mammalian neural development in vivo signal to the growth cone cytoskeleton during axon outgrowth and guidance. In this review we describe our recent work in dissociated cultures of developing rodent sensorimotor cortex in the context of the current literature on molecular guidance cues, calcium signaling pathways and cytoskeletal dynamics that regulate growth cone behaviors. A major challenge is to relate findings in tissue culture to mechanisms of cortical development in vivo. Toward this goal, we describe our recent work in cortical slices, which preserve the complex cellular and molecular environment of the mammalian brain but allow direct visualization of growth cone behaviors and calcium signaling. Findings from this work suggest that mechanisms regulating axon growth and guidance in dissociated culture neurons also underlie development of cortical connectivity in vivo.